Influence Training, Work Motivation and Discipline Work on Employee Performance at PT Summit Seoyon Automotive Indonesia - Zurotun Nisa Nur Auliah; Gopar, Ida Abdul (Jurnal Ilmiah Sumber Daya Manusia, 2024)
In reach the goal , something organization need source Power man as manager system . Source Power humans are also factor central in management something organization . Those who become mover wheel organization in achieve and realize the goals and objectives set . Study This aim For know influence training, work motivation and discipline Work to Kinejra employee at PT Summit Seoyon Automotuve Indonesia. Study This use method quantitative , with sample of 60 respondents . Data analysis includes : validity test , reliability test , assumption test classic , analysis multiple linear regression and hypothesis . Test result First obtained that training No influential to performance employees , proven with results  t count of 0.982 < value t table 2.003 and sig of 0.330. Testing second , work motivation influential to performance employees , with results mark t count amounting to 4.358 < value t table 2.003 and sig of 0.000. Test result third  discipline Work influential to performance employees , proven with t count of 5.709 < value t table 2.003 and sig of 0.000.